IMPROVING STUDENTS’ VOCABULARY BY USING BOOKLETS - Agustiawan, Agustiawan; Sofian, Sofian; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe seventh Grade of Madrasah Tsanawiyah Negeri 2 Pontianak in academic year 2017/2018 had problems in vocabulary. It could be seen from several indicators: first, their vocabulary score was low. Second, students did not have motivation during teaching-learning process. To overcome the problems, the researcher designed a class action that was applied to the 40 students of class 7B Madrasah Negeri 2 Pontianak. The researcher used booklets to improve students? vocabulary. There were two cycles of action. In each cycle, the procedure of the research consists of planning, acting, observing, and reflecting. The result of the research shows that booklets could improve the students? vocabulary. Based on observation checklist, field notes, and test result, the students made improvement in vocabulary. The students could learn vocabulary easier than before. They could memorize and understand the English word easily. When the booklets are used, in the first cycle and second cycle, students were enthusiastic in joining learning activity. Students were also active as group members when they did the group work. The result of the study was that the students? progress during teaching and learning activity in cycle 1 and cycle 2.Key Words: Improving, Vocabulary, Booklets.